2017
DOI: 10.1002/jor.23747
|View full text |Cite
|
Sign up to set email alerts
|

Palovarotene inhibits connective tissue progenitor cell proliferation in a rat model of combat‐related heterotopic ossification

Abstract: Heterotopic ossification (HO) develops in the extremities of wounded service members and is common in the setting of high-energy penetrating injuries and blast-related amputations. No safe and effective prophylaxis modality has been identified for this patient population. Palovarotene has been shown to reduce bone formation in traumatic and genetic models of HO. The purpose of this study was to determine the effects of Palovarotene on inflammation, progenitor cell proliferation, and gene expression following a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Cell titration experiments determined that under the conditions employed, skeletogenic differentiation of R206H-FAPs requires transplantation of >20,000 cells, and above this threshold number, mean HO volume was proportional to the number of R206H-FAPs transplanted ( Figure 6—figure supplement 1 ). Given that palovarotene ( Chakkalakal et al, 2016 ; Wheatley et al, 2018 ) and activin A ( Namwanje and Brown, 2016 ) can affect cell proliferation and survival in other contexts, we first characterized population growth dynamics of wild-type and R206H-FAPs following transplantation, and subsequently tested whether palovarotene treatment and sequestration of activin A influenced population growth of R206H-FAPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell titration experiments determined that under the conditions employed, skeletogenic differentiation of R206H-FAPs requires transplantation of >20,000 cells, and above this threshold number, mean HO volume was proportional to the number of R206H-FAPs transplanted ( Figure 6—figure supplement 1 ). Given that palovarotene ( Chakkalakal et al, 2016 ; Wheatley et al, 2018 ) and activin A ( Namwanje and Brown, 2016 ) can affect cell proliferation and survival in other contexts, we first characterized population growth dynamics of wild-type and R206H-FAPs following transplantation, and subsequently tested whether palovarotene treatment and sequestration of activin A influenced population growth of R206H-FAPs.…”
Section: Resultsmentioning
confidence: 99%
“…RARγ agonists have been shown to dampen BMP signaling by reducing SMAD1/5/8 phosphorylation ( Shimono et al, 2011 ), potentially by increasing proteasome-mediated SMAD degradation, as has been shown for all- trans -retinoic acid ( Sheng et al, 2010 ). These effects likely explain, at least in part, the inhibitory effects of RARγ agonists on chondrogenic and osteogenic differentiation in BMP-induced and genetic models of HO ( Chakkalakal et al, 2016 ; Inubushi et al, 2018 ; Shimono et al, 2014 ; Shimono et al, 2011 ; Sinha et al, 2016 ; Wheatley et al, 2018 ). Intriguingly, pretreating bone marrow-derived mesenchymal stem cells with the RARγ agonists CD1530 ( Shimono et al, 2011 ) or NRX204647 ( Shimono et al, 2014 ) blocked BMP2-induced skeletogenic differentiation, possibly by reprogramming these cells to a non-skeletal lineage ( Shimono et al, 2014 ; Shimono et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…While we do acknowledge that we should examine the actions of palovarotene and RARγ agonists on other chondrosarcoma cell lines and primary chondrosarcomas before making a definitive conclusion, our results suggest, however, that RARγ signaling may be a possible targeted pathway. Palovarotene, an orally bioavailable and selective RARγ agonist, has been identified as having therapeutic action against FOP, heterotopic ossification, and osteochondroma, but has not been characterized previously for chondrosarcoma . Notably, palovarotene is orally bioavailable, has been well‐tolerated in clinical trials, and is currently under investigation in phase 3 (NCT03312634) and phase 2 (NCT03442985) clinical trials for FOP and multiple osteochondroma, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Palovarotene, an agonist of RARγ, a nuclear RA receptor, has effects on cartilage biology and has been demonstrated to play a critical role in the inhibition of heterotopic ossification . Furthermore, preclinical studies have demonstrated that palovarotene is a potent inhibitor of ectopic cartilage formation in rodent models of both acquired and genetic heterotopic ossification and have shown inhibition of growth of benign cartilage tumors in an osteochondroma animal model . Notably, palovarotene is currently being investigated in phase 3 clinical trials for the treatment of fibrodysplasia ossificans progressiva (FOP) (http://Clinicaltrials.gov registration NCT02190747, phase 3) and multiple osteochondromas (NCT03442985, phase 2).…”
mentioning
confidence: 99%
“…Successful decreased inflammation, osteogenic and chondrogenic gene expression, and connective tissue progenitor cell proliferation with an oral-gavage delivered retinoic acid receptor-γ , palovarotene, in an established HO blast-injury model has demonstrated promise in future studies. 73 Additionally, orally delivered palovarotene demonstrated at least 50% decrease in polytrauma, infection-induced HO. 74 Intraperitoneal delivery of rapamycin on an established blast-injury model has been reported to successfully inhibit HO formation with no reported wound-healing complications.…”
Section: Future Considerationsmentioning
confidence: 98%